2018
DOI: 10.1096/fj.201801690r
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ERBB4 rejuvenates aged mesenchymal stem cells and enhances angiogenesis via PI3K/AKT and MAPK/ERK pathways

Abstract: The age‐related functional exhaustion limits potential efficacy of mesenchymal stem cells (MSC) in treating cardiovascular disease. Therefore, rejuvenation of aged MSC in the elderly population is of great interest. We have previously reported that Erb‐B2 receptor tyrosine kinase 4 (ERBB4) plays a critical role in regulating MSC survival under hypoxia. The aim of this study was to investigate whether ERBB4 rejuvenates aged MSC and how ERBB4 enhances therapeutic efficacy of aged MSC in treating myocardial infar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 33 publications
4
83
0
Order By: Relevance
“…Among the various types of stem cells currently used in pre-clinical and clinical trials, MSCs have been considered a favourable cell source for MI treatment because of their unique advantages, such as easy isolation, low immunogenicity and multipotent differentiation capacity. 20,22 However, most MSCs died within 3 days after transplantation in the harsh environment of the injured heart, thus limiting therapeutic efficacy. 23 Recently, accumulating evidence has demonstrated pharmacological pre-treatment as a novel strategy to promote the survival of transplanted BM-MSCs in the ischaemic heart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various types of stem cells currently used in pre-clinical and clinical trials, MSCs have been considered a favourable cell source for MI treatment because of their unique advantages, such as easy isolation, low immunogenicity and multipotent differentiation capacity. 20,22 However, most MSCs died within 3 days after transplantation in the harsh environment of the injured heart, thus limiting therapeutic efficacy. 23 Recently, accumulating evidence has demonstrated pharmacological pre-treatment as a novel strategy to promote the survival of transplanted BM-MSCs in the ischaemic heart.…”
Section: Discussionmentioning
confidence: 99%
“…Female C57/B6J mice, 6‐8 weeks old, were purchased from the Shanghai Laboratory Animal Research Center (Shanghai, China). An MI model in mice was developed as previously described . After ligation of the left anterior descending artery (LAD) 2 mm from the aorta, randomly chosen mice received an intramyocardial injection of 30 µL of PBS (MI group, n = 15), 3.0 × 10 5 BM‐MSCs in 30 μL PBS (BM‐MSC group, n = 13) or 3.0 × 10 5 haemin‐pretreated BM‐MSCs in 30 μL PBS (haemin‐BM‐MSC group, n = 12) at four sites on the surrounding border of the infarct area.…”
Section: Methodsmentioning
confidence: 99%
“…We also observed that transplantation of AMSCs had a lower therapeutic efficacy for MI in mice compared with transplantation of YMSCs. Indeed, rejuvenating aged MSCs to increase their therapeutic efficacy for cardiovascular diseases has attracted a lot of attention, and several novel strategies have been explored to rejuvenate aged MSCs, including gene modification (Liang et al, 2019; Song et al, 2017) and pharmacological pretreatment (Fang et al, 2018). However, the potential mechanisms underlying MSC senescence remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Human YMSCs and AMSCs were isolated from the bone marrow of young and aged volunteer donors, respectively, as previously described (Liang et al, 2019). Written informed consent was obtained from all donors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation